Exterior view of Temple 3 - Temples of India Project Team (Jio Institute, 2024)
The temple has a pitha (a small platform) and vedibandha (basal mouldings) that includes a khura, kumbha (pot-shaped), kalasha (a pitcher), antarapatta (recesses between mouldings), and kapotapalikas (cyma recta mouldings). The jangha (wall) is plain, with the gates carved at its centre. The shikhara (superstructure) above the varandika (moulded parapet) features an anekandaka shikhara (multispired superstructure) with surasenaka (miniature spires) on all four sides.